Methane carbon dioxide reforming catalyst, preparation method thereof and methane carbon dioxide reforming reaction method

By synthesizing porous CeO2 support in methane carbon dioxide reforming catalyst using the template method and contacting it with the La-Ni perovskite precursor, La-Ni perovskite oxide is generated, which solves the problems of insufficient catalyst activity, poor stability and poor carbon deposit resistance, and achieves efficient catalytic activity and carbon deposit resistance.

CN119633797AActive Publication Date: 2025-03-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311181792.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-18
Estimated Expiration
2043-09-13

AI Technical Summary

Technical Problem

The existing methane carbon dioxide reforming catalysts have insufficient activity, poor stability, and poor carbon deposit resistance.

Method used

The template method was used to synthesize porous CeO2 support, and contacted with the CeO2 support using the La-Ni perovskite precursor to form La-Ni perovskite oxide on the surface of CeO2 to form a catalyst.

Benefits of technology

The catalyst's catalytic activity and carbon deposit resistance are significantly improved, the conversion rate of methane and carbon dioxide is improved, and the amount of carbon deposit in the catalyst is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633797A_ABST
    Figure CN119633797A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, and discloses a methane and carbon dioxide reforming catalyst, a preparation method thereof and a methane and carbon dioxide reforming reaction method, the preparation method comprises the following steps: (1) in the presence of a first solvent, mixing a soluble compound of Ce, a porous carbon material and a first complexing agent to obtain a first mixture; the specific surface area of the porous carbon material is 50-400m < 2 > / g; (2) carrying out reaction on the first mixture to form gel, and then carrying out first roasting to obtain a CeO2 carrier; and (3) enabling a La-Ni perovskite precursor to be in contact with the CeO2 carrier, and then performing second roasting. According to the method, a porous CeO2 carrier is synthesized by adopting a template method, La-Ni perovskite oxide is generated on the surface of CeO2, the prepared catalyst is applied to methane carbon dioxide reforming reaction, and the catalytic activity and carbon deposition resistance of the catalyst can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a methane carbon dioxide reforming catalyst and a preparation method thereof, and a methane carbon dioxide reforming reaction method. Background Art

[0002] In recent years, with the continuous development of industry, the amount of CO2 emissions in the atmosphere has increased, leading to global warming. The effective resource utilization of CO2 can not only reduce CO2 emissions, but also provide a new resource for social development.

[0003] Methane CO2 reforming to produce synthesis gas is an effective way to utilize CO2. It also uses relatively cheap natural gas to produce synthesis gas (CO+H2), which can be further converted into other downstream hydrocarbon products with high added value. However, the biggest problem with this reaction process is that the catalyst used in methane CO2 reforming to produce synthesis gas is mainly nickel-based catalyst, which is prone to carbon deposition. If the carbon deposition problem cannot be effectively solved, it will seriously limit the stability of the catalyst and the industrialization process.

[0004] Perovskite has become the focus of attention in many fields because of its excellent electrical conductivity, magnetism, thermoelectricity, piezoelectricity and many other properties, low preparation cost, thermodynamic and mechanical stability at high temperature. Perovskite composite oxide materials are excellent oxygen ion and electron conductors under high temperature conditions, can also release oxygen under inert conditions, and can replenish oxygen through the Redox (redox) process. Therefore, using perovskite oxide as a catalyst for the methane carbon dioxide reforming reaction can effectively eliminate carbon deposits on the catalyst surface, thereby helping to improve the catalyst's ability to resist carbon deposition. However, the activity and anti-carbon deposition performance of the catalyst are still not very ideal. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of insufficient activity, poor stability and poor anti-carbon deposition performance of methane carbon dioxide reforming catalysts in the prior art, and to provide a methane carbon dioxide reforming catalyst and a preparation method thereof, and a method for methane carbon dioxide reforming reaction. The catalyst prepared by the preparation method has good anti-carbon deposition ability and good catalytic activity.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a methane carbon dioxide reforming catalyst, the preparation method comprising:

[0007] (1) In the presence of a first solvent, a soluble compound of Ce, a porous carbon material and a first complexing agent are mixed to obtain a first mixture; the specific surface area of ​​the porous carbon material is 50-400 m 2 / g;

[0008] (2) reacting the first mixture to form a gel, and then performing a first calcination to obtain a CeO2 carrier;

[0009] (3) contacting the La-Ni perovskite precursor with the CeO2 carrier, and then performing a second calcination.

[0010] Preferably, based on the total amount of the CeO2 carrier and the La-Ni perovskite precursor calculated as LaNiO3, the content of the CeO2 carrier is 20-60wt%, preferably 30-50wt%; the content of the La-Ni perovskite precursor calculated as LaNiO3 is 40-80wt%, preferably 50-70wt%;

[0011] Preferably, the preparation method of the La-Ni perovskite precursor comprises: mixing a La source, a Ni source and a solvent under stirring in the presence of a second complexing agent, wherein the mixing temperature is 30-80° C. and the mixing time is 6-13 h.

[0012] The second aspect of the present invention provides a methane carbon dioxide reforming catalyst prepared by the above preparation method.

[0013] A third aspect of the present invention provides a method for methane carbon dioxide reforming reaction, comprising: under reforming reaction conditions, contacting methane and carbon dioxide with a catalyst, wherein the catalyst is the above-mentioned methane carbon dioxide reforming catalyst.

[0014] The preparation method provided by the present invention first uses a template method to synthesize a porous CeO2 carrier, and then uses a La-Ni perovskite precursor to contact the CeO2 carrier. The inventor of the present invention found in the study that the La-Ni perovskite precursor is used to contact with porous CeO2 to generate La-Ni perovskite oxide on the surface of CeO2. The obtained catalyst is used in the methane carbon dioxide reforming reaction, which can significantly improve the catalytic activity and anti-carbon deposition ability of the catalyst. The reason may be that CeO2 with a certain number of pores and pore structure can form a strong interaction with the particles in the La-Ni perovskite precursor, which can not only improve the dispersibility of the La-Ni perovskite oxide, but also effectively control the crystal structure of the perovskite oxide. At the same time, it fully utilizes the large number of oxygen vacancies contained in cerium dioxide and the specific semiconductor properties of the perovskite oxide to achieve effective synergy of the two characteristics and significantly improve the electron transfer ability of the active center of the perovskite oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the XRD pattern of the catalyst prepared in Example 1;

[0016] Figure 2 It is the stability evaluation curve of the catalysts prepared in Examples 1, 2 and Comparative Example 1. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] A first aspect of the present invention provides a method for preparing a methane carbon dioxide reforming catalyst, the preparation method comprising:

[0019] (1) In the presence of a first solvent, a soluble compound of Ce, a porous carbon material and a first complexing agent are mixed to obtain a first mixture; the specific surface area of ​​the porous carbon material is 50-400 m 2 / g;

[0020] (2) reacting the first mixture to form a gel, and then performing a first calcination to obtain a CeO2 carrier;

[0021] (3) contacting the La-Ni perovskite precursor with the CeO2 carrier, and then performing a second calcination.

[0022] According to the present invention, a porous carbon material is first used as a template CeO2 carrier, and the pore structure of the CeO2 carrier is adjusted by using a porous carbon material with an appropriate number of pores. Then, a La-Ni perovskite precursor is contacted with the CeO2 carrier to generate La-Ni perovskite oxide on the surface of CeO2. The catalyst is used in the methane carbon dioxide reforming reaction, which can significantly improve the catalytic activity and anti-carbon deposition ability of the catalyst. The reason may be that CeO2 with a certain number of pores and pore structure can form a strong interaction with the particles in the La-Ni perovskite precursor, which can not only improve the dispersibility of the La-Ni perovskite oxide, but also significantly improve the electron transfer ability of the active center of the perovskite oxide.

[0023] In the present invention, a specific surface area of ​​50-400m 2 / g of porous carbon material is used as a template, and a CeO2 carrier is prepared by using a porous carbon material with a certain number of pores as a template. After a first calcination to remove the porous carbon material, a CeO2 carrier with an appropriate pore structure can be formed. CeO2 with a certain number of pores and pore structure can form a strong interaction with the particles in the La-Ni perovskite precursor, which can not only improve the dispersibility of the La-Ni perovskite oxide, but also significantly improve the electron transfer ability of the active center of the perovskite oxide, thereby improving the catalytic activity and anti-carbon deposition performance of the catalyst.

[0024] In the present invention, the specific surface area of ​​the porous carbon material can be 50-400m 2 / g, for example, 50m 2 / g, 60m 2 / g,70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 250m 2 / g, 280m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g or other typical and limiting specific surface area values ​​or the range between the two. Preferably, the specific surface area of ​​the porous carbon material is 100-250m 2 / g. The porous carbon material with the above preferred specific surface area is used to prepare CeO2 with a suitable pore structure, thereby improving the dispersion ability of perovskite oxide on the surface of CeO2 and the synergistic ability between the two, which is beneficial to further improve the catalytic activity and anti-carbon deposition performance of the catalyst.

[0025] In some preferred embodiments, the porous carbon material has a relatively regular pore structure, preferably, the average pore size of the porous carbon material is 5-20 nm, preferably 8-15 nm. In the above preferred case, it is beneficial to standardize the pore structure of CeO2, and then standardize the crystal structure and grain size of the perovskite oxide.

[0026] In the present invention, the specific surface area and average pore size of the porous carbon material are measured by a nitrogen adsorption characterization method.

[0027] The present invention has a wide range of selection for the specific types of the porous carbon material. Any porous carbon material having the above-mentioned number of pores and pore structure and capable of being removed by subsequent calcination can be applied to the present invention. The present invention has no particular limitation on the source of the porous carbon material, which can be purchased from a commercial source or prepared by any method known in the art. The present invention has no particular requirements for the shape of the porous carbon material, as long as the above-mentioned pore structure requirements are met. Preferably, the porous carbon material is selected from at least one of activated carbon, carbon nanotubes and carbon fibers. The carbon nanotubes can be single-walled carbon nanotubes and / or double-walled carbon nanotubes.

[0028] Preferably, the particle diameter of the activated carbon is 50-100 μm.

[0029] Preferably, the carbon nanotubes have a diameter of 5-20 nm and a length of 100-300 nm.

[0030] Preferably, the carbon fiber has a fiber diameter of 10-60 μm and a fiber length of 0.5-2 mm.

[0031] In the present invention, by controlling the amount of porous carbon material and soluble Ce compounds, the pore structure of the CeO2 carrier can be further optimized, which is beneficial to further improve the interaction between CeO2 and La-Ni perovskite in the prepared catalyst and improve the anti-carbon deposition performance. Preferably, the mass ratio of the porous carbon material to the soluble compound of Ce calculated as CeO2 is (0.05-2):1, for example, it can be 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1 and other typical but non-limiting masses or ranges therebetween. Preferably, the mass ratio of the porous carbon material to the soluble compound of Ce calculated as CeO2 is (0.2-1):1.

[0032] In the present invention, the introduction of the first complexing agent is conducive to the full fusion between the cerium precursor and the carbon material, and a good binding force is formed during the reaction process, thereby giving full play to the role of the carbon material pore template agent.

[0033] According to the present invention, preferably, the molar ratio of the soluble Ce compound to the first complexing agent, calculated as Ce element, is (0.5-3):1, preferably (1-2):1.

[0034] Preferably, the first complexing agent is selected from citric acid and / or ethylenediaminetetraacetic acid.

[0035] In the present invention, there is no particular limitation on the mixing conditions of step (1), as long as the components can be fully mixed. Preferably, the mixing temperature of step (1) is 30-80°C, preferably 30-70°C, and the mixing time is 1-6h, preferably 3-5h.

[0036] In the present invention, there is no particular requirement for the order of mixing in step (1). The Ce soluble compound, the porous carbon material and the first complexing agent can be added to the first solvent together for mixing, or the first complexing agent and the porous carbon material can be added to the first solvent for one-step mixing, and then the Ce soluble compound is added for two-step mixing. Preferably, the first complexing agent and the porous carbon material are first added to the first solvent for one-step mixing for 1-2 hours, and then the Ce soluble compound is added for two-step mixing for 2-4 hours. The temperature of the one-step mixing and the two-step mixing can be the same or different, and both meet the above-mentioned mixing conditions.

[0037] According to the present invention, the reaction conditions in step (2) are based on the ability to form a gel. Preferably, the reaction conditions in step (2) include: a temperature of 60-90°C, preferably 70-90°C; and a time of 8-20h, preferably 8-12h.

[0038] Preferably, the method further comprises: drying the gel and then performing the first calcination. The present invention has no particular limitation on the drying conditions, as long as the gel can be dried. Preferably, the drying temperature is preferably 100-120°C.

[0039] Preferably, the conditions for the first calcination in step (2) include: a temperature of 500-800° C., preferably 500-600° C., and a time of 6-20 h, preferably 6-12 h.

[0040] The present invention has a wide range of choices for the first solvent in step (1), preferably, the first solvent is water. The present invention also has no particular limitation on the amount of the solvent, as long as the components are fully dispersed and mixed.

[0041] In the present invention, the selection range of the soluble compound of Ce is relatively wide, as long as it can provide the Ce element, it can be selected from soluble organic salts and / or inorganic salts of Ce. Preferably, the soluble compound of Ce is selected from at least one of cerium nitrate, cerium acetate and cerium oxalate.

[0042] The soluble compound of Ce may also contain crystal water, which is well known to those skilled in the art.

[0043] In the present invention, La-Ni perovskite has a perovskite crystal structure, and its molecular formula can be expressed as LaNiO3; the La-Ni perovskite precursor refers to a mixture that can obtain La-Ni perovskite by gelation and roasting, and can be a solution or a sol. Preferably, the La-Ni perovskite precursor is in a sol state. The above preferred embodiment is used to further improve the dispersibility of La-Ni perovskite on the surface of the CeO2 carrier, and further improve the activity and anti-carbon deposition performance of the catalyst.

[0044] In a further preferred embodiment, the preparation method of the La-Ni perovskite precursor comprises: mixing a La source, a Ni source and a solvent under stirring conditions in the presence of a second complexing agent, wherein the mixing temperature is 30-80°C and the time is 1-8 hours. The La-Ni perovskite precursor prepared by the above preferred preparation method is in contact with a CeO2 carrier, which is conducive to achieving full fusion between the perovskite and CeO2, thereby enhancing the synergistic effect between the two.

[0045] Preferably, the mixing temperature is 30-50°C and the mixing time is 3-6h.

[0046] In the present invention, the mixing method may be to first dissolve the second complexing agent in a solvent and then mix it with the La source and the Ni source. Preferably, the stirring rate is 100-200 rpm.

[0047] Preferably, the second complexing agent is selected from citric acid and / or ethylenediaminetetraacetic acid.

[0048] According to some preferred embodiments of the present invention, the molar ratio of the Ni source to the La source, calculated as metal elements, is (0.5-2):1, preferably (0.5-1.5):1.

[0049] Preferably, the molar ratio of the total molar amount of the La source and the Ni source calculated as metal elements to the second complexing agent is 0.5-3:1, preferably 0.6-2:1.

[0050] Preferably, the amount of the solvent used is such that the total concentration of the La source and the Ni source calculated as metal elements is 0.3-2 mol / L, preferably 1-2 mol / L.

[0051] In the present invention, the specific types of the La source and the Ni source can be selected in a wide range, and any soluble organic salt or inorganic salt of a metal can be applied to the present invention, for example, at least one of a nitrate, an acetate and an oxalate of a metal can be selected. The La source and the Ni source can also contain crystal water, which is well known to those skilled in the art.

[0052] Preferably, the contact temperature in step (3) is 60-90°C, preferably 60-80°C.

[0053] According to the present invention, in step (3), the La-Ni perovskite precursor is contacted with the CeO2 carrier in a manner including: mixing the La-Ni perovskite precursor with the CeO2 carrier under stirring conditions. The present invention has no special requirements for the mixing conditions, as long as the La-Ni perovskite precursor and the CeO2 carrier are mixed uniformly.

[0054] The present invention has a wide selection range for the solvent, which can be the same as the selection range of the first solvent.

[0055] According to the present invention, preferably, the prepared catalyst comprises a CeO2 carrier and La-Ni perovskite, and the molecular formula of the La-Ni perovskite can be expressed as LaNiO3.

[0056] According to some preferred embodiments of the present invention, based on the total amount of the CeO2 carrier and the La-Ni perovskite precursor calculated as LaNiO3, the content of the CeO2 carrier is 20-60wt%, preferably 30-50wt%; for example, it can be 30wt%, 35wt%, 40wt%, 45wt%, 50wt% and other typical but non-limiting content values ​​or the range between the two; the content of the La-Ni perovskite precursor calculated as LaNiO3 is 40-80wt%, preferably 50-70wt%, for example, it can be 50wt%, 55wt%, 60wt%, 65wt%, 70wt% and other typical but non-limiting content values ​​or the range between the two.

[0057] Preferably, the second calcination is performed at a temperature of 500-800° C., preferably 500-600° C., for a time of 6-20 h, preferably 8-12 h.

[0058] According to a preferred embodiment of the present invention, the preparation method comprises:

[0059] S1. In the presence of a first solvent, a soluble compound of Ce, a porous carbon material and a first complexing agent are mixed to obtain a first mixture; the specific surface area of ​​the porous carbon material is 100-250 m 2 / g;

[0060] S2, reacting the first mixture to form a gel, and then performing a first calcination to obtain a CeO2 carrier;

[0061] S3, under stirring conditions, in the presence of a second complexing agent, mixing a La source, a Ni source and a solvent to obtain a La-Ni perovskite precursor; the mixing temperature is 30-50° C., and the time is 3-6 hours;

[0062] S4, contacting the La-Ni perovskite precursor with the CeO2 carrier, and then performing a second calcination.

[0063] The adoption of the above preferred implementation method is conducive to further improving the interaction between La-Ni perovskite and the carrier in the catalyst and improving the ability to resist carbon deposition. The reason for this may be that CeO2 with a certain number of pores and pore structure can form a strong interaction with the particles in the La-Ni perovskite precursor, which can not only improve the dispersibility of La-Ni perovskite oxide, but also effectively control the crystal structure of perovskite oxide. At the same time, it makes full use of the large number of oxygen vacancies contained in cerium dioxide and the specific semiconductor properties of perovskite oxide to achieve effective synergy of the two characteristics, which can significantly improve the electron transfer ability of the active center of perovskite oxide. This effectively avoids the cracking and carbon deposition of methane during the reaction process. At the same time, even if a small amount of carbon deposition is generated on the catalyst surface, due to the special electronic properties of the catalyst, the carbon deposition can react quickly with the generated during the reaction to achieve the elimination of carbon deposition.

[0064] The second aspect of the present invention provides a methane carbon dioxide reforming catalyst prepared by the above preparation method.

[0065] According to the present invention, the catalyst includes a CeO2 carrier and a La-Ni perovskite loaded on the CeO2 carrier. Preferably, based on the total amount of the catalyst, the content of the CeO2 carrier is 20-60wt%, preferably 30-50wt%, for example, it can be 30wt%, 35wt%, 40wt%, 45wt%, 50wt% and other typical but non-limiting content values ​​or the range between the two; the content of the La-Ni perovskite is 40-80wt%, preferably 50-70wt%, for example, it can be 50wt%, 55wt%, 60wt%, 65wt%, 70wt% and other typical but non-limiting content values ​​or the range between the two. It is understood that when the catalyst consists only of a CeO2 carrier and a La-Ni perovskite loaded on the CeO2 carrier, the sum of the contents of the two meets the 100% principle.

[0066] A very small amount of NiO may also exist in the catalyst, and the content of NiO is negligible in the present invention.

[0067] In the present invention, the content of each component in the catalyst is tested and obtained by an X-ray fluorescence spectroscopy (XRF) characterization method.

[0068] X-ray diffraction (XRD) characterization method proved the presence of La-Ni perovskite structure in the catalyst.

[0069] Preferably, the specific surface area of ​​the catalyst is 50-250m 2 / g, preferably 100-180m 2 / g.

[0070] A third aspect of the present invention provides a method for methane carbon dioxide reforming reaction, comprising: under reforming reaction conditions, contacting methane and carbon dioxide with a catalyst, wherein the catalyst is the methane carbon dioxide reforming catalyst provided in the second aspect.

[0071] Preferably, the reforming reaction conditions include: a molar ratio of methane to carbon dioxide of 1:1-1.5, preferably 1:1.2-1.5, a reaction temperature of 700-950°C, preferably 750-900°C; a pressure of 0.1-0.5MPa, preferably 0.1-0.3MPa, and a carbon volume space velocity of the feed gas of 1000-6000h -1 , preferably 2000-5000h -1 .

[0072] According to some preferred embodiments of the present invention, the method further comprises: before the contacting, reducing the catalyst under a hydrogen atmosphere.

[0073] Preferably, the reduction conditions include: temperature of 400-600° C., preferably 450-550° C.; time of 2-20 h, preferably 5-12 h; pressure of 0.1-0.5 MPa, preferably 0.1-0.3 MPa.

[0074] Preferably, the hydrogen atmosphere can be provided by hydrogen or a mixture of hydrogen and an inert gas, and the inert gas can be selected from nitrogen and / or argon. Preferably, in the mixture of hydrogen and an inert gas, the volume content of hydrogen is 5-20%.

[0075] The present invention will be described in detail below through examples.

[0076] Unless otherwise specified, the raw materials used were purchased from commercial sources.

[0077] Example 1

[0078] (1) Dissolve 50 g of citric acid in water to form a solution, add 50 g of multi-walled carbon nanotubes (purchased from Aladdin, with a tube diameter of 10-15 nm, a length of 100-150 nm, and a specific surface area of ​​200 m 2 / g, average pore size of 10nm) was poured into citric acid solution and stirred at 30℃ for 1h. 126g of cerium nitrate hexahydrate was dissolved in distilled water and dropped into the above solution, and stirred for 3h at 30℃. Then the temperature was raised to 80℃ and stirred for 10h to evaporate the water to obtain a gel. The obtained gel was dried at 100℃. The dried product was placed in a muffle furnace and calcined at 600℃ for 6h in an air atmosphere to obtain porous CeO2.

[0079] (2) Dissolve 100 g of citric acid in water to obtain a complexing agent solution. Dissolve 88 g of lanthanum nitrate hexahydrate and 59 g of nickel nitrate hexahydrate in water to obtain a lanthanum nitrate solution and a nickel nitrate solution, respectively. Then, drop the above aqueous solutions into the complexing agent solution, respectively. The amount of water used is such that the total concentration of the La source and the Ni source in terms of metal elements in the obtained mixed solution is 1 mol / L. Stir at 40° C. for 6 hours to form a sol.

[0080] (3) Under stirring conditions, 40 g of porous CeO2 was mixed with the above sol at a contact temperature of 80°C to evaporate water and obtain a gel. The obtained gel was dried at 120°C. The dried product was placed in a muffle furnace and calcined at 600°C for 8 hours to obtain a catalyst named CAT-1. The composition and structural parameters of the catalyst are shown in Table 1.

[0081] The obtained catalyst was characterized by XRD. Figure 1 As shown, it can be seen that the catalyst includes CeO2 and LaNiO3 with a perovskite structure. In addition, there is a characteristic peak of NiO in the range of 2θ of 35-45°, which is relatively sharp and narrow, indicating that the NiO content is small and its content is negligible.

[0082] Example 2

[0083] (1) Dissolve 50 g of citric acid in water to form a solution, add 20 g of activated carbon (purchased from Aladdin, with a particle diameter of 50-100 μm and a specific surface area of ​​200 m 2 / g, average pore size 8nm) was poured into citric acid solution and stirred at 30℃ for 1h. 126g of cerium nitrate hexahydrate was dissolved in distilled water and dropped into the above solution, and stirred for 3h at 30℃. Then the temperature was raised to 90℃ and stirred for 8h to evaporate the water to obtain a gel. The obtained gel was dried at 110℃. The dried product was placed in a muffle furnace and calcined at 600℃ for 6h in an air atmosphere to obtain porous CeO2.

[0084] (2) Dissolve 100 g of citric acid in water to obtain a complexing agent solution. Dissolve 60 g of lanthanum nitrate hexahydrate and 40 g of nickel nitrate hexahydrate in water to obtain a lanthanum nitrate solution and a nickel nitrate solution, respectively. Then, drop the above solutions into the complexing agent solution, respectively. The amount of water used is such that the total concentration of the La source and the Ni source in terms of metal elements in the obtained mixed solution is 1 mol / L. Stir at 50° C. for 3 h to obtain a sol.

[0085] (3) Under stirring conditions, 40 g of porous CeO2 was contacted with the above-mentioned La-Ni perovskite precursor at a contact temperature of 80°C to evaporate the water and obtain a gel. The obtained gel was dried at 120°C. The dried product was placed in a muffle furnace and calcined at 600°C for 8 hours to obtain a catalyst named CAT-2. Its XRD pattern is similar to Figure 1 Similarly, the composition and structural parameters of the catalysts are shown in Table 1.

[0086] Example 3

[0087] (1) 80 g of citric acid was dissolved in water to form a solution, and 20 g of carbon fiber (purchased from Aladdin, with a fiber diameter of 10-60 μm, a fiber length of 0.5-2 mm, and a specific surface area of ​​120 m 2 / g, average pore size of 10nm) was poured into citric acid solution and stirred at 30℃ for 1h. 200g of cerium nitrate hexahydrate was dissolved in distilled water and dropped into the above solution, and stirred for 3h at 30℃. Then the temperature was raised to 90℃, stirred for 8h to evaporate the water and obtain a gel. The obtained gel was dried at 120℃. The dried product was placed in a muffle furnace and calcined at 600℃ for 12h in an air atmosphere to obtain porous CeO2.

[0088] (2) Dissolve 100 g of citric acid in water to obtain a complexing agent solution. Dissolve 80 g of lanthanum nitrate hexahydrate and 40 g of nickel nitrate hexahydrate in 200 mL of water to obtain a lanthanum nitrate solution and a nickel nitrate solution, and then drop the above solutions into the complexing agent solution. The amount of water used is such that the total concentration of the La source and the Ni source in terms of metal elements in the obtained mixed solution is 1 mol / L. Stir at 30° C. for 6 hours to form a sol.

[0089] (3) Pour 40g of porous CeO2 into the above sol under stirring, and evaporate the water at 80°C to obtain a gel. The obtained gel is dried at 120°C. The dried product is placed in a muffle furnace and calcined at 600°C for 8h to obtain a catalyst named CAT-3. Its XRD pattern is similar to Figure 1 The composition and structural parameters of the catalyst are shown in Table 1.

[0090] Example 4

[0091] The method of Example 1 is followed, except that the mass of the multi-walled carbon nanotubes used is 5 g.

[0092] The prepared catalyst is recorded as CAT-4. The composition and structural parameters of the catalyst are shown in Table 1.

[0093] Example 5

[0094] The method of Example 1 is followed, except that the specific surface area of ​​the multi-walled carbon nanotubes used is 60 m 2 / g, with an average pore diameter of 30nm (tube diameter of 20-35nm, length of 100-300nm, purchased from Aladdin Company).

[0095] The prepared catalyst is recorded as CAT-5. The composition and structural parameters of the catalyst are shown in Table 1.

[0096] Example 6

[0097] According to the method of Example 1, except that steps (2) and (3) are not performed, 100 g of citric acid is dissolved in water to obtain a complexing agent solution. 88 g of lanthanum nitrate hexahydrate, 59 g of nickel nitrate hexahydrate and 40 g of porous CeO2 obtained in step (1) are added to the above solution, stirred at 40°C for 6 hours, then heated to 80°C and stirred for 8 hours to evaporate water to obtain a gel. The obtained gel is dried at 120°C. The dried product is placed in a muffle furnace and calcined at 600°C for 8 hours to obtain a catalyst named CAT-6. The composition and structural parameters of the catalyst are shown in Table 1.

[0098] Comparative Example 1

[0099] Dissolve 100g of citric acid in water to obtain a complexing agent solution. Dissolve 88g of lanthanum nitrate hexahydrate and 59g of nickel nitrate hexahydrate in water to obtain lanthanum nitrate solution and nickel nitrate solution, respectively, and then drop the above aqueous solutions into the complexing agent solution, and the amount of water used is such that the total concentration of the La source and Ni source in terms of metal elements in the obtained mixed solution is 1mol / L. Stir at 40°C for 6h to form a sol. Then heat to 80°C, stir for 9h to evaporate water, and obtain a gel. Dry the obtained gel at 120°C. Place the dried product in a muffle furnace and roast at 600°C for 8h to obtain a LaNiO3 catalyst. Named DCAT-1. The composition and structural parameters of the catalyst are shown in Table 1.

[0100] Comparative Example 2

[0101] (1) Dissolve 100g of citric acid in water to form a solution, pour 20g of multi-walled carbon nanotubes into the solution, and stir at 30°C for 1h. Dissolve 126g of cerium nitrate hexahydrate in distilled water and drop into the above solution, and stir thoroughly at 30°C for 3h. Then heat to 80°C and stir for 9h to evaporate the water to obtain a gel. The obtained gel is dried at 100°C. The dried product is placed in a muffle furnace and calcined at 600°C for 6h in an air atmosphere to obtain porous CeO2.

[0102] (2) Dissolve 100g of citric acid in a certain amount of water to obtain a complexing agent solution. Dissolve 59g of nickel nitrate hexahydrate in water and add it to the complexing agent solution. The amount of water used is such that the concentration of Ni element in the obtained mixed solution is 1 mol / L. Stir at 40°C for 6h. Add 40g of porous CeO2 obtained in step (1) to the above solution. Then heat it to 80°C, evaporate the water under stirring, and obtain a gel. Dry the obtained gel at 120°C. Place the dried product in a muffle furnace and roast it at 600°C for 8h to obtain a NiO catalyst supported by porous CeO2. Named DCAT-2. The composition and structural parameters of the catalyst are shown in Table 1.

[0103] Comparative Example 3

[0104] (1) Dissolve 50g of citric acid in water to form a solution, dissolve 126g of cerium nitrate hexahydrate in distilled water and drop into the solution, and stir thoroughly at 30°C for 3h. Then heat to 80°C and stir for 10h to evaporate the water to obtain a gel. The obtained gel is dried at 100°C. The dried product is placed in a muffle furnace and calcined at 600°C for 6h in an air atmosphere to obtain CeO2.

[0105] (2) Dissolve 100 g of citric acid in water to obtain a complexing agent solution. Dissolve 88 g of lanthanum nitrate hexahydrate and 59 g of nickel nitrate hexahydrate in water to obtain a lanthanum nitrate solution and a nickel nitrate solution, respectively. Then, drop the above aqueous solutions into the complexing agent solution, respectively. The amount of water used is such that the total concentration of the La source and the Ni source in terms of metal elements in the obtained mixed solution is 1 mol / L. Stir at 40° C. for 6 hours to form a sol.

[0106] (3) Under stirring conditions, 40 g of CeO2 was mixed with the above sol at a temperature of 80°C to evaporate the water and obtain a gel. The obtained gel was dried at 120°C. The dried product was placed in a muffle furnace and calcined at 600°C for 8 hours to obtain a catalyst named DCAT-3. The composition and structural parameters of the catalyst are shown in Table 1.

[0107] Table 1

[0108] serial number <![CDATA[Content of CeO2 carrier, wt%]]> Content of La-Ni perovskite wt% <![CDATA[Specific surface area m 2 / g]]> CAT-1 34 66 150.1 CAT-2 43 57 169.3 CAT-3 36 64 160.2 CAT-4 34 66 80.6 CAT-5 34 66 50.3 CAT-6 34 66 45.6 DCAT-1 0 100 10.5 DCAT-2 73 0(the rest is NiO) 169.1 DCAT-3 34 66 40.2

[0109] Catalyst Evaluation:

[0110] The catalyst performance was evaluated in a fixed-bed reactor at atmospheric pressure.

[0111] 300 mg of the catalyst prepared above (40-60 mesh) was mixed evenly with 1.5 g of quartz sand (40-60 mesh) and put into a steel tube, and the steel tube reactor was fixed in a heating furnace. Programmed temperature reduction was carried out for 10 hours in a mixed atmosphere of N2 (20 mL / min) and H2 (20 mL / min). The reduction temperature was 450°C and the pressure was 0.1 MPa.

[0112] After the reduction is completed, the raw gas is switched to a molar ratio of methane to carbon dioxide of 1:1.2, the reaction temperature is 750°C, and the carbon volume space velocity is 20,000 h -1 , the pressure is normal pressure.

[0113] After 20 hours of reaction, the product was collected, and the product composition was analyzed by gas chromatography, and the CO2 conversion rate and CH4 conversion rate were calculated. The carbon deposition amount of the catalyst was tested by the thermogravimetric method under air atmosphere, and the results are shown in Table 2. The stability evaluation curves of the catalysts prepared in Examples 1, 2 and Comparative Example 1 are shown in Table 2. Figure 2 shown.

[0114]

[0115]

[0116] Table 2

[0117] serial number <![CDATA[CH4 conversion rate (%)]]> <![CDATA[CO2 conversion rate (%)]]> Carbon deposit amount mg / gcat CAT-1 89.3 83.6 0.21 CAT-2 85.1 81.2 0.43 CAT-3 86.3 80.5 0.54 CAT-4 84.2 81.2 0.36 CAT-5 83.5 82.1 0.65 CAT-6 82.1 79.6 0.96 CAT-7 79.6 78.6 1.02 DCAT-1 61.2 30.5 8.03 DCAT-2 40.2 10.5 15.96 DCAT-3 45.2 23.8 10.36

[0118] It can be seen from the results in Table 2 that the present invention uses La-Ni perovskite precursor to contact with porous CeO2 to generate La-Ni perovskite oxide on the surface of CeO2. The prepared catalyst is used in the methane carbon dioxide reforming reaction, which can significantly improve the catalytic activity and anti-carbon deposition ability of the catalyst, and the conversion rate of methane and carbon dioxide is high and the carbon deposition amount is low.

[0119] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a methane carbon dioxide reforming catalyst, characterized in that: The preparation method comprises: (1) In the presence of a first solvent, a soluble compound of Ce, a porous carbon material and a first complexing agent are mixed to obtain a first mixture; the specific surface area of ​​the porous carbon material is 50-400 m 2 / g; (2) reacting the first mixture to form a gel, and then performing a first calcination to obtain a CeO2 carrier; (3) contacting the La-Ni perovskite precursor with the CeO2 carrier, and then performing a second calcination.

2. The preparation method according to claim 1, wherein The specific surface area of ​​the porous carbon material is 100-250 m 2 / g; Preferably, the average pore size of the porous carbon material is 5-20 nm, preferably 8-15 nm; Preferably, the porous carbon material is selected from at least one of activated carbon, carbon nanotubes and carbon fibers.

3. The preparation method according to claim 1 or 2, wherein The mass ratio of the porous carbon material to the soluble compound of Ce calculated as CeO2 is (0.05-2):1, preferably (0.2-1):1; Preferably, the molar ratio of the Ce soluble compound to the first complexing agent is (0.5-3):1, preferably (1-2):1; Preferably, the first complexing agent is selected from citric acid and / or ethylenediaminetetraacetic acid.

4. The preparation method according to any one of claims 1 to 3, wherein The mixing temperature in step (1) is 30-80° C. and the mixing time is 1-6 h; Preferably, the reaction conditions in step (2) include: temperature of 60-90°C and time of 8-20h; Preferably, the conditions for the first calcination in step (2) include: a temperature of 500-800° C., preferably 500-600° C., and a time of 6-20 h, preferably 6-12 h.

5. The preparation method according to any one of claims 1 to 4, wherein: The La-Ni perovskite precursor is in a sol state; Preferably, the preparation method of the La-Ni perovskite precursor comprises: mixing a La source, a Ni source and a solvent under stirring conditions in the presence of a second complexing agent, wherein the mixing temperature is 30-80° C. and the mixing time is 1-8 hours; Preferably, the second complexing agent is selected from citric acid and / or ethylenediaminetetraacetic acid.

6. The preparation method according to claim 5, wherein: Calculated as metal elements, the molar ratio of the Ni source to the La source is (0.5-2):1, preferably (0.5-1.5):1; Preferably, the molar ratio of the total molar amount of the La source and the Ni source calculated as metal elements to the second complexing agent is 0.5-3:1; Preferably, the amount of the solvent used is such that the total concentration of the La source and the Ni source calculated as metal elements is 0.3-2 mol / L.

7. The preparation method according to any one of claims 1 to 6, wherein: The CeO2 carrier and the total amount of the La-Ni perovskite precursor calculated as LaNiO3 are used as the basis, the content of the CeO2 carrier is 20-60wt%, preferably 30-50wt%; the content of the La-Ni perovskite precursor calculated as LaNiO3 is 40-80wt%, preferably 50-70wt%; Preferably, the contact temperature in step (3) is 60-90°C; Preferably, the second calcination is performed at a temperature of 500-800° C., preferably 500-600° C., for a time of 6-20 h, preferably 8-12 h.

8. A methane carbon dioxide reforming catalyst obtained by the preparation method according to any one of claims 1 to 7.

9. A method for methane carbon dioxide reforming reaction, characterized in that: include: Under reforming reaction conditions, methane and carbon dioxide are contacted with a catalyst, wherein the catalyst is the methane carbon dioxide reforming catalyst as claimed in claim 8.

10. The method according to claim 9, wherein: The reforming reaction conditions include: a molar ratio of methane to carbon dioxide of 1:(1-1.5), a reaction temperature of 750-950°C, a pressure of 0.1-0.5 MPa, and a carbon volume space velocity of the feed gas of 1000-6000 h -1 .

Citation Information

Patent Citations

  • Supported catalyst for methane three-reforming reaction and preparation method and application of supported catalyst

    CN103949265A

  • Methane and carbon dioxide reforming nickel-based catalyst and preparation method and application thereof

    CN113413908A

  • Anti-carbon-deposition methane and carbon dioxide reforming catalyst and preparation method thereof

    CN114471581A

  • LaCeNiO perovskite catalyst with ultra-wide Ni (111) crystal face as well as preparation method and application of LaCeNiO perovskite catalyst

    CN114713235A

  • Preparation method and application of nickel / cerium oxide catalyst

    CN114733528A